Enhancing an immersive horror game by measuring presence: a sentiment analysis - dos Santos, Matheus Augusto Souza; Leite, Regina Maria Cunha; Ferreira, Yasmim Thasla; Winkler, Ingrid; Cordeiro, André Martins; Machado, Luiz Claudio (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This study investigates the integration of horror game design elements within immersive virtual reality environments to enhance presence effects through Design Science Research methodology. The developed artifact, “Ecos do Pelourinho,” is a culturally authentic VR horror experience combining atmospheric environmental design, spatial audio implementation, and strategic horror mechanics using Unity 6 and Blender. The system applies environmental storytelling with integrated world canvas UI systems for narrative delivery. Evaluation employed semi-structured interviews grounded in presence theory constructs, analyzing responses from four participants through systematic thematic analysis. Results demonstrate that cultural authenticity amplifies presence, as participants exhibited immediate environmental recognition and sustained emotional engagement. Findings establish horror-enhanced presence effects as empirically valid, contributing to spatial presence theory and offering replicable methodologies for immersive VR research and applications in training, therapeutic intervention, and entertainment contexts.